Young professionals´ neuropsychological functioning when using alcohol as a leisure activity - Flores, Pablo (2020)
Nowadays, it is common for young professionals to use alcohol as a recreational activity after their weekly work day; although, this habit would be related to neuropsychological alterations. Aim. The aim is to analyze the effect of alcohol consumption once a week on young professionals´ neuropsychological functioning. Method. Quantitative, with a quasi-experimental design and cross-sectional study, where a group of 30 young professionals who consume alcohol once a week, is compared with a control group of 32 healthy young professionals who do not consume alcohol. Results. It was found that professionals in the consumer group showed lower performance in neuropsychological tests that assessed cognitive flexibility, initiative, phonological fluency, reading, similarities, viso-spatial memory and recognition. Conclusions. Results suggest that weekly alcohol consumption generates a negative impact on young professionals´ neuropsychological functioning, which may produce a counterproductive effect in the contexts where they operate. Results are discussed around previous research and highlighting the need to identify the negative effect of alcohol consumption once a week, which would seem like a pleasurable activity for young professionals, although, this habit could negatively impact on their cognitive performance. © Health and Addictions 2020